ABSTRACT - SANTOSO, BAMBANG EKO; WI, INPURWANTO; HURRIYANI, YENI (Jurnal Sains Mahasiswa Pertanian, 2020)
Stingray is an important fisheries commodity in North Kayong. Continuous stingrays catching results in the extinction of several stingray species. This study was conducted to determine the species composition, index of species diversity, dominance, uniformity, abundance and conservation status of rays at Sukadana Fishing port, North Kayong Regency. The method used in this study was a descriptive survey. The results of the study found 291 individual stingrays consisting of 14 species and 2 families. The results showed that the highest relative abundance is the Telatrygon zugei species with a value of 0.213 and the lowest abundance of stingrays are the Neotrygon kuhlii species with a value of 0.007, the index of stingray diversity (H) 2,371 classified as moderate, the uniformity index (E) 0.898 classified as high, the dominance index (C) 0.003 classified as low. Based on the IUCN Red List of Threatened Species, there are 6 species of stingrays are included in the category of Vulnerable (VU), 4 species are in the category of Near Threatened (NT), 2 species are in the category of Not Evaluated (NE), and 2 species are in the category of Data Deficient (DD).